Coronary Angiography Findings in Patients at Robert Wolter Monginsidi Hospital, Manado, Indonesia - Kurniawan Fatoni; Daniela Angeline; Janry Antonius Pangemanan (Cermin Dunia Kedokteran, 2016)
Background: Acute coronary syndromes at young age would subsequently lead to morbidity and mortality in productive age. This study was intended to identify coronary angiography findings difference in young and old patients. Method: A descriptive study using medical record of patients who underwent coronary angiography at Robert Wolter Monginsidi Third Level Hospital, Manado, between December 2014 and June 2015 was done. The defined angiography findings in this study is artery with significant stenosis (stenosis ≥ 70%) and sum of blood vessels with significant stenosis (vessel score). Patients were categorized into young age group (≤ 45 years old) and old age group (> 45 years old). Results were presented in descriptive tables. Results: Among 133 patients, stenosis was mainly found in Left Anterior Descending Artery (LAD) in both groups (37.5% in young age and 72.6% in old age group). No significant stenosis in Left Main Coronary Artery (LMCA) in young age group whereas there were 10.3% cases in old age group. Normal / non – significant angiograms were higher in young age group compared to old age group (62.5% versus 20.5%). The proportion of patients with triple-vessel disease were higher in old age group compared to young age group (27.4% versus 6.3%). Conclusion: LAD artery stenosis was the most common stenosis found in both groups. Most patients in young age group had normal angiograms, whereas old age group had a higher percentage of triple-vessel disease and stenosis in LMCA.Latar Belakang: Sindrom Koroner Akut di usia muda akan menyebabkan morbiditas dan mortalitas pada usia produktif. Studi ini bertujuan untuk mengetahui perbedaan gambaran angiografi koroner pada pasien berusia muda dan tua. Metode: Studi deskriptif data rekam medik pasien yang menjalani angiografi koroner di Rumah Sakit Tingkat III Robert Wolter Monginsidi Manado, dari Desember 2014 hingga Juni 2015). Pasien dibagi menjadi kelompok usia muda (≤ 45 tahun) dan kelompok usia tua (> 45 tahun). Gambaran angiografi yang dicatat adalah arteri dengan penyempitan signifikan (stenosis ≥ 70%) dan jumlah pembuluh darah yang mengalami penyempitan signifikan (skor pembuluh darah). Hasil disajikan secara deskriptif. Hasil: Dari 133 pasien, penyempitan paling banyak dijumpai di Left Anterior Descending Artery (LAD) (37.5% pada kelompok usia muda dan 72.6% pada kelompok usia tua). Penyempitan signifikan Left Main Coronary Artery (LMCA) tidak ditemukan di kelompok usia muda, sedangkan di kelompok usia tua terdapat 10.3% kasus. Angiogram normal / non – signifikan lebih banyak pada kelompok usia muda dibandingkan kelompok usia tua (62.5% berbanding 20.5%). Triple-vessel disease lebih sering dijumpai pada kelompok usia tua dibandingkan kelompok usia muda (27.4% berbanding 6.3%). Simpulan: LAD merupakan arteri koroner yang paling banyak mengalami penyempitan di kedua kelompok. Mayoritas kelompok usia muda memiliki angiogram normal, kelompok usia tua memiliki persentase triple-vessel disease dan penyempitan LMCA lebih tinggi.